CRIMINAL LIABILITY FOR A DENTIST'S NEGLIGENCE THAT CAUSES INJURY TO A PATIENT IS BASED ON LAW NUMBER 17 OF 2023 CONCERNING HEALTH - Najib Albana Daulay; Fitri Rafianti; Bambang Fitrianto (PT. Radja Intercontinental Publishing, 2024)
The profession as a dentist is not easy because many dentists in the world often commit malpractice acts. Law Number 17 of 2023 concerning Health regulates the qualifications and types of dental malpractice acts. Problems include how negligence by dentists in carrying out their duties is categorized as malpractice and is a criminal act, factors that cause dentists to be negligent in carrying out their duties and how criminal liability for dentist negligence which causes injuries to patients is reviewed from Law Number 17 of 2023 About health. The type of research used in this research is normative legal research. The nature of the research used in this research is descriptive. A dentist's negligence in carrying out their duties which results in injury to a patient can be categorized as malpractice and a criminal act. This occurs when dentists do not comply with professional standards, standard operating procedures, or applicable codes of ethics, which harms patients. The factors that cause dentists to be negligent in carrying out their duties include several important aspects, namely the negligence factor (culpa), the deliberate factor, the misunderstanding factor (dwaling), the error of judgment factor, the contributory negligence factor and the infrastructure factors. Criminal liability for a dentist's negligence which causes injury to a patient is reviewed by Law Number 17 of 2023 Health, regulated in Article 440 of the Law, punishable by a maximum imprisonment of 3 years or a maximum fine of IDR 250,000,000. If the negligence causes death, the sentence can increase to a maximum prison term. 5 years or a maximum fine of IDR 500,000,000. Researchers recommend that dentists regularly participate in training and education regarding professional standards, standard operating procedures (SOP). So that dentists increase awareness regarding the responsibility for negligence which can result in injury to patients..